Asymptomatic thrombosis of extrahepatic portal vein aneurysm necessitating hybrid operative repair. (October 2021) - Gorolay, Vineet; Nguyen, Daniel; Samra, Jaswinder; Neale, Michael
Background: Congenital portal vein aneurysm is a rare vascular anomaly with poorly understood natural history. Whereas asymptomatic aneurysms are often managed conservatively, surgery has been used in symptomatic cases complicated by thrombosis or rupture. Surgical experience in management of portal aneurysms is restricted to case studies with limited comparative data and inconsistent reporting of outcomes. A hybrid open and endovascular approach has rarely been described in the literature. Methods: We present a case of an extrahepatic portal aneurysm which demonstrated changes on surveillance imaging concerning for early asymptomatic thrombosis. Acute thrombus was identified at the time of open aneurysm repair. We review the limited literature regarding management of portal vein aneurysms in non-cirrhotic patients. Results: Our case was complicated by intrahepatic thrombo-embolism, which necessitated hybrid thrombectomy and anticoagulant therapy. The patient remains asymptomatic at three-year follow-up with no recurrent aneurysm or thrombosis on surveillance Doppler and CT imaging. Conclusions: Altered hemodynamic appearances on Doppler ultrasound and contrast-enhanced CT may warn of impending thrombosis in portal vein aneurysms. Hybrid open and endovascular surgical repair ensures vessel patency and a durable surgical result.